Quality of life and associated factors among women with obstetric fistula in Ethiopia - Biruktawit Matiwos; Getachew Tesfaw; Asmare Belete; Dessie Abebaw Angaw; Shegaye Shumet (BMC, 2021)
Abstract Background Obstetric fistula is an abnormal opening between the vagina and bladder or rectum. Women affected by obstetric fistula are often abandoned by their husbands, stigmatized by the community, physically debilitated and blamed for their conditions. These factors lead the victims to low self esteem, depression and prolonged emotional trauma. The physical, emotional and social suffering associated with continuous leakage of urine has a profound impact on women quality of life. The aim of this study was to assess quality of life and associated factors among obstetric fistula patients in Ethiopia, and it will have a significant role for further intervention. Objective To assess quality of life and associated factors among obstetric fistula patients in Ethiopia, 2017. Methods Institution based cross-sectional study design was conducted at fistula centers in Ethiopia. Systematic sampling technique was used to recruit a total of 289 women with obstetric fistula. The World Health Organization Quality of Life-Brief (WHOQOL-BREF) Version was used to assess quality of life. We computed simple and multiple linear regression analysis to assess factors associated with quality of life and P-value < 0.05 was declared statistically significant. Adjusted unstandardized β coefficient of multiple linear regressions was used to describe associated factors of quality of life. Result Of 289 women studied, only 12.1% felt satisfied with their general state of health and quality of life. In the physical health domain, the mean quality of life score was 40.78 ± .78. In the psychological domain, the mean quality of life score was 39.96 ± .82. In the social and environmental domain, the mean quality of life score was 32.9 ± .95, 36.45 ± .8, respectively. Duration of incontinence (β =  − 3.8,95% CI(− 6.95, − .62), patients coming for surgical procedure (β =  − 4.4, 95% CI(− 7.64, − 1.2), poor social support(β =  − 6.14, 95%CI (− 8.8, − 3.4), co-morbid anxiety (β =  − 4, 95% CI (− 7,-1.1) and depression (β =  − 9.2, 95% CI (− 12, − 6.4) were negatively associated with physical domain of quality of life. Co-morbid anxiety (β =  − 11,95% CI (− 14.8, − 7.3), employment (β = 9.1,95% CI (.5, 17.6), number of children(β = 2.1,95%CI(.8, 3.4), and depression(β =  − 6.3,95%CI(− 9.7, − 2.9) were associated with a psychological domain. Duration of incontinence (β =  − 8.1, 95%CI(− 12.82, − 3.4), poor social support (β =  − 7.8(− 12, − 3.6), patients coming for surgical procedure (β =  − 12, 95%CI (− 17.4, − 6.4) and co-morbid anxiety (β =  − 9.2, 95% CI (− 13.8, 4.5) were negatively associated with social domain of quality of life. Number of children present (β = 2.4, 95%CI (.82, 3.6), and poor social support (β =  − 5.5, 95%CI (− 9.5, − 1.5) were significantly associated with an environmental domain of quality of life. Conclusion and recommendation Co-morbid depression and anxiety, poor social support, duration of urine incontinence, employment, number of children, and duration of hospital stay were factors significantly associated with domains of QOL. Treating co-morbid depression and anxiety, and social support are necessary to increase women's quality of life. In addition, it is better to have a plane of income generation victims, and awareness creation about early treatment of the problem for community by the concerned body to improve women quality of life.